ANALISIS PENGARUH STRATEGI PRAKERIN DAN MINAT KERJA TERHADAP KESIAPAN KERJA PESERTA DIDIK MENENGAH KEJURUAN - Helen Libastari (ADIBA : JOURNAL OF EDUCATION, 2024)
This research aims to determine the role of schools, especially vocational secondary education, in facilitating students through internships to enter the world of work. The research method used is a qualitative method, namely qualitative data obtained from library research or literature studies from various sources. The research results show that vocational secondary education plays a very big role. An important role in integrating students into the world of work. However, schools cannot guarantee 100% because students' success in finding work depends on their personal skills and competencies. The school tries to provide various facilities such as career guidance and industrial work practices (Prakerin) to students.